2013
DOI: 10.1089/aid.2012.0119
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS-Associated Opportunistic Protozoal Diarrhea

Abstract: Human immunodeficiency virus (HIV) infection has altered both the epidemiology and outcome of enteric opportunistic parasitic infections. This study was done to determine the prevalence and species/genotypes of intestinal coccidian and microsporidial infections among HIV/AIDS patients with diarrhea and/or a history of diarrhea alternately with an asymptomatic interval, and their association with CD4 T cell count. This crosssectional study was done from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 38 publications
(38 reference statements)
5
79
0
Order By: Relevance
“…Oral-anal and oral genital contact predisposes homosexuals to infection with enteric pathogens. 35 IPI was higher among PLHA having CD 4 -T cell counts <200/µl than having ≥200/µl, which shows agreements with reports from other countries regarding IPI in different CD 4 ranges 25,28,36,37 as well as from Nepal. 4,38 In studies conducted in Nepal, more than three-fifth to four-fifth of the HIV patients with CD 4 T-cell count <200 were found having parasitic infections.…”
Section: Discussionsupporting
confidence: 86%
“…Oral-anal and oral genital contact predisposes homosexuals to infection with enteric pathogens. 35 IPI was higher among PLHA having CD 4 -T cell counts <200/µl than having ≥200/µl, which shows agreements with reports from other countries regarding IPI in different CD 4 ranges 25,28,36,37 as well as from Nepal. 4,38 In studies conducted in Nepal, more than three-fifth to four-fifth of the HIV patients with CD 4 T-cell count <200 were found having parasitic infections.…”
Section: Discussionsupporting
confidence: 86%
“…C. andersoni is a gastric parasite which has been associated with reduced milk yield in dairy cattle and decreased weight gain in post weaned calves (Olson et al 2004) and is occasionally detected in humans (Leoni et al, 2006;Morse et al, 2007;Waldron et al, 2011;Agholi et al, 2013;Jiang et al, 2014;Liu et al, 2014). Two studies in China by the same research group have reported that C. andersoni was the most prevalent Cryptosporidium species detected in humans Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, C. andersoni is recognized as one of the most common opportunistic and non-opportunistic pathogens HIV/AIDS patient with chronic diarrhea [13]. In China, C. andersoni was the dominant species in cattle [14].…”
Section: The Studymentioning
confidence: 99%